The impact agenda and the study of British politics. Issue 3 (3rd September 2018) - Hayton, Richard
Abstract This article attempts to discern the nature of impact in relation to the British politics sub-field of political studies. It reviews evidence from REF2014 to establish how political scientists working in this area understood and tried to demonstrate impact. It critically appraises how the impact agenda is affecting how research into British politics is prioritised, undertaken and disseminated, and questions whether this is a good thing for the sub-discipline. The implications of this for the shape of British politics research going forward are considered. While welcoming the possibility of a re-centring of scholarly attention on British politics, the article cautions against a retreat to the parameters of the British Political Tradition and the Westminster Model view.